ANALISIS PENDIDIKAN, PENGALAMAN KERJA DAN PELATIHAN PADA PELAYANAN APARATUR PAJAK DI UPTD SAMSAT AMURANG - Regah, Ryan T.; Sabijono, Harijanto; Pinatik, Sherly (GOING CONCERN : JURNAL RISET AKUNTANSI, 2019)
In essence, the main task of the government as a public organization is to provide services to the community. Likewise with SAMSAT Amurang as one of the public organizations that are directly related to public services. SAMSAT has the duty to serve the community in terms of managing payments for Motor Vehicle Taxes (PKB) and Taxes on Transfer of Motor Vehicles (BBNKB). The tax sector is an important sector in national development, because most of the development is financed from PKB and BBNKB sectors and then increase, one of hte factors is due to the increasing number of taxpayers who pay taxes. Every day SAMSAT serves hundreds of taxpayers. By increasing the number of these taxpayers can SAMSAT withdraw taxes which in turn will be used for state financing. As one of its contributions SAMSAT strives to provide the best service in accordance with the expectations and needs of the community as taxpayers.